The Indonesian Executives Perspective of CSR Practices (Issues in Social and Environmental Accounting (ISEA), 2014)
The objective of this study is to investigate the CSR (Corporate Social Responsibility) practices after the issuance of the government regulation as the implementation guideline of the CSR as stipulated in the law no.40/2007 through business players’ interviews. Using the semistructured interviews with Indonesian executives/informants of Indonesian companies, this study found that CSR practices have been viewed as philanthropic activities of companies with all the consequences that follow: shareholder as the most important stakeholder, reporting CSR practice as means to have public image and no need to have any standard to prepare CSR practice reporting. Given the findings, there is a need to redefine CSR based on the intention to maintain good relationship with stakeholders and to have the integrated management system to help management well interact with them in market and non-market mechanism.